1999
DOI: 10.1021/bi990836i
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Transition State Complementarity in the Hydrolysis of O-Arylphosphorothioates by Protein-Tyrosine Phosphatases

Abstract: The hydrolysis of O-arylphosphorothioates by protein-tyrosine phosphatases (PTPases) was studied with the aim of providing a mechanistic framework for the reactions of this important class of substrate analogues. O-Arylphosphorothioates are hydrolyzed 2 to 3 orders of magnitude slower than O-aryl phosphates by PTPases. This is in contrast to the solution reaction where phosphorothioates display 10-60-fold higher reactivity than the corresponding oxygen analogues. Kinetic analyses suggest that PTPases utilize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
84
1
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 70 publications
6
84
1
2
Order By: Relevance
“…The PTPase catalyzed reaction proceeds through a double displacement mechanism in which the phosphoryl group from the substrate is first transferred to the active site Cys residue, leading to the formation of a cysteinyl phosphate intermediate that is subsequently hydrolyzed by water. The guanidinium group of the active site Arg makes two hydrogen bonds with two phosphoryl oxygens in the substrate and plays an important role in substrate binding and transition state stabilization (28,29). A unique feature of PTPase catalysis is the use of a conserved Asp residue as a general acid (30), which is brought into position for catalysis by a movement of a flexible loop that occurs upon binding of substrate (31)(32)(33).…”
Section: Fig 4 Effect Of Ph On the Omfp Hydrolysis Reaction Catalyzmentioning
confidence: 99%
“…The PTPase catalyzed reaction proceeds through a double displacement mechanism in which the phosphoryl group from the substrate is first transferred to the active site Cys residue, leading to the formation of a cysteinyl phosphate intermediate that is subsequently hydrolyzed by water. The guanidinium group of the active site Arg makes two hydrogen bonds with two phosphoryl oxygens in the substrate and plays an important role in substrate binding and transition state stabilization (28,29). A unique feature of PTPase catalysis is the use of a conserved Asp residue as a general acid (30), which is brought into position for catalysis by a movement of a flexible loop that occurs upon binding of substrate (31)(32)(33).…”
Section: Fig 4 Effect Of Ph On the Omfp Hydrolysis Reaction Catalyzmentioning
confidence: 99%
“…The PTPases utilize the Cys in the signature motif as a nucleophile in the formation of a thiophosphoryl covalent enzyme intermediate (9,10). The invariant Arg residue in the PTPase signature motif functions in substrate binding and in transition state stabilization (11)(12)(13). The initial phosphoryl transfer from the substrate to the enzyme is assisted by a conserved Asp on a surface loop, which protonates the leaving group (14,15), thereby acting as a general acid catalyst.…”
mentioning
confidence: 99%
“…It has been shown that the cysteine residue in this motif functions as a nucleophile, attacking the substrate phosphate atom directly and displacing the leaving group to form a phosphocysteine intermediate (17)(18)(19)(20)(21)(22). The arginine in this motif has been shown to be particularly important for transition state stabilization (23)(24)(25) and is essential for catalysis (26 -28). For Cdc25B, the cysteine and arginine in the PTPase signature motif have been shown by site-directed mutagenesis to be required for catalysis (29).…”
mentioning
confidence: 99%